Design of novel nozzles for higher interlayer strength of 3D printed cement paste - He, Lewei (2022)
In this study, novel nozzles for cement paste 3D printing are designed and optimized for higher interlayer strength via experiment and volume-of-fluid (VOF) based simulation, in terms of various outlet shapes and two nozzle components namely the interface shaper and the side trowel. These nozzles are evaluated experimentally and theoretically based on their performances in the specimen interlayer strength, interfacial shear stress, and cross-sectional geometry. It is concluded that the “Cir3” and the “Kidney” outlet shapes achieve the best performance with the paste water-cement (w/c) ratio ranging from 0.21 to 0.23, subject to the nozzle stand-off distance of 12 mm and printing speed of 60 mm/s. In addition, the interface shaper and the side trowel are able to further enhance the interlayer strength significantly by up to 2 times, through optimization of the interfacial geometry and minimization of the interlayer notch of 3D printed cement paste. It is also confirmed that the optimal nozzle varies with the w/c ratio of cement paste due to different notch depths that are generated, such that nozzle optimization is required along with material development for cement paste 3D printing.